153 Do pre and postnatal nutrition interact to program reproductive phenotype in sexually mature heifers?. (30th November 2020) - Maia, Tatiane S; Guimarães, Higor R; Franco, Gessica A; Pohler, Ky G; Cardoso, Rodolfo C; Williams, Gary L
Abstract: Objectives were to test the hypothesis that nutritional extremes during pregnancy in the bovine female negatively affect phenotypic characteristics of the estrous cycle of sexually mature offspring, and to determine whether these effects interact with postnatal diets during the juvenile period. Beginning at 90 d of pregnancy, Brangus and Braford (n = 108) beef cows with a female fetus were fed to achieve body condition scores of 7.5–8 (H, obese), 5–5.5 (M, moderate) or 3–3.5 (L, very thin) by the start of the third trimester. Heifer offspring were weaned and fed to gain at either a high (H; 1 kg/d) or low (L; 0.5 kg/d) rate between 4 and 8 months of age, then fed a common growth diet until puberty. Estrous cycles of a subgroup (n = 53) were synchronized using 2 injections of prostaglandin F2α(PGF). Transrectal ultrasonography was employed during the follicular phase of two estrous cycles to evaluate antral follicle count(AFC), rate of growth and size of the ovulatory follicle, size of corpus luteum(CL), and endometrial thickness. Blood samples were collected daily for assay of plasma concentrations of progesterone(P4) and estradiol-17β(E2) by RIA. Preliminary data (n = 35) were analyzed using ANOVA and mixed model procedures. Least Squares Means estrous cycle length (20.9 ± 0.2 days), AFC (19.7 ± 1.0), follicular growth rate (0.81 ± 0.11), ovulatory follicle size (12.8 ± 0.2 mm), CL size (16.8 ± 0.6 mm), and endometrial thickness (14.6 ± 0.3 mm) did not differ among treatments. Heifers in postnatal H group tended (P < 0.1) to have a greater area (arbitrary units) under the E2 curve (12.6 ± 0.6) than postnatal L (11.3 ± 0.5) during the follicular phase. Normalized AUC for P4 was greater (P < 0.03) in L/H (56.94 ± 3.22) than both M/H (42.98 ± 3.61) and L/L (43.66 ± 3.22) groups. Despite marked pre- and postnatal nutritional contrasts, independent and interactive effects of nutritional treatments have been of minor significance or undetectable to date.